The Open Balkan Initiative: Pioneering Regional Cooperation or a Transient Political Experiment? - Ushkovska, Mare (International Problems, 2026)
The Open Balkan Initiative is an interesting case study of the effectiveness of dissemination of Schengen-like arrangements beyond the EU, particularly as a locally initiated enterprise of intergovernmental coordination. Grounded in the new regionalism theory and the tenets of international political economy, this study explores the potential and limits of such an arrangement in the Western Balkans, analyses its accomplishments, the concerns regarding its suitability for purpose, and the likely trajectory of this regional integration initiative. Through a qualitative explanatory analysis, this case study seeks to address the following central question: can Open Balkan be considered a successful regional integration initiative and, if so, to what extent? The findings show that, while there is little to differentiate Open Balkan’s ideas from previous similar multilateral initiatives, the initiative has shown faster progress in implementing its agreements compared to the Berlin Process. The study also analyses the political stigma surrounding Open Balkan and challenges some of the criticism present in previous literature. It argues that the Open Balkan’s limited membership is a strength, enabling the three member countries to implement agreements more readily, such as that on the common labour market, unburdened by many of the unresolved bilateral political disputes present in the region. Yet, the initiative is vulnerable to political cycles, as leaders’ disinterest in recent years has underscored the unclear long-term framework and sustainability of regional policy coordination between member states.
Keywords: regional cooperation; Western Balkans; EU integration; freedom of movement; common labour market